Certain Subclass of Harmonic Univalent Functions Associated With Fractional Calculus Operator - Puneet Shukla,; A. L. Pathak, (International Journal of Scientific Research in Science and Technology, 2024)
In this paper, a class of complex-valued harmonic univalent functions f (z) in the open disk U is defined by fractional calculus operator. We obtained coefficient bounds, distortion inequalities, convex combination, extreme points and convolution conditions for this class.
Keywords: Harmonic functions; Univalent functions; Fractional Calculus Operator